Front Cover: Antibody–Prodrug Conjugates with KSP Inhibitors and Legumain‐Mediated Metabolite Formation (Chem. Eur. J. 35/2019). Issue 35 (26th April 2019) - Lerchen, Hans‐Georg; Stelte‐Ludwig, Beatrix; Berndt, Sandra; Sommer, Anette; Dietz, Lisa; Rebstock, Anne‐Sophie; Johannes, Sarah; Marx, Leo; Jörißen, Hannah; Mahlert, Christoph; Greven, Simone
Abstract : In the lysosome, legumain (LGMN in the picture) is required to release the active KSPi‐metabolite from antibody–prodrug conjugates, in addition to complete antibody degradation. High LGMN expression in solid tumors compared with healthy tissue may lead to drugs with further increased tumor selectivity and lower off‐target toxicity. More information can be found in the Communication by H.‐G. Lerchen et al. on page 8208 . The authors thank the graphic designers at The New Atlantic (Cologne) and Jürgen Franz for designing the cover image.